Analysis of Public Reception of Nujek - Arifin, M Saiful; Hariyanto, Didik (Indonesian Journal of Public Policy Review, 2022)
Analysis of Public Reception of Nujek. This study examines how the public's understanding and acceptance of Nujek. This research uses reception analysis theory and brand image. The purpose of this study was to determine the public's reception of Nujek's services. This research is descriptive and the method used is qualitative with data collection techniques using open and in-depth interviews consisting of 11 informants. The results of this study indicate that the public reception of Nujek resulted in two conclusions, namely the first understanding of the community already knowing Nujek from social media Instagram and Facebook, billboards and friend recommendations. So based on these results the public's understanding of Nujek shows the position of Dominant Hegemony. Second, where the informants show results that they want to use Nujek because the price is cheap for customers, the driver select service feature for customers, can subscribe and attractive commissions for driver partners. However, due to the lack of stability and the distribution of drivers that are less than optimal, the community is not satisfied with Nujek's services, so based on these results the public's acceptance of Nujek shows a Negotiated position.